2006
DOI: 10.1007/s00401-006-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein structure, posttranslational modification and alternative splicing as aggregation enhancers

Abstract: Alpha-synuclein aggregation is thought to be a key event in the pathogenesis of synucleinopathies. Although different alpha-synuclein alterations and modifications have been proposed to be responsible for early aggregation steps, the mechanisms underlying these events remain unclarified. Alpha-synuclein is a small protein localized to synaptic terminals and its intrinsic structure has been claimed to be an important factor for self-oligomerization and self-aggregation. Alpha-synuclein expression studies in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 135 publications
3
163
0
14
Order By: Relevance
“…The physiological function of AS is still elusive (3,4). Research is mainly focused on the etiology of a series of neurologic disorders known as synucleinopathies, first among them is Parkinson disease.…”
Section: ␣-Synuclein (As)mentioning
confidence: 99%
“…The physiological function of AS is still elusive (3,4). Research is mainly focused on the etiology of a series of neurologic disorders known as synucleinopathies, first among them is Parkinson disease.…”
Section: ␣-Synuclein (As)mentioning
confidence: 99%
“…This difference could be explained by alternative splicing of SNCA transcript, which results in formation of two differently sized mRNAs of 339 and 420 bps in length. It is known that at least three isoforms of α-syn are produced via alternative splicing [3]. The major form of the protein, and the one most investigated, is the 140 aminoacids-long transcript.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has, however, suggested that it might form, in the cell, a dynamic tetramer that is not prone to aggregation [107]. Three regions can be distinguished in the aSyn sequence [106,108] ( Fig. 5A).…”
Section: Human A-synuclein and Parkinson's Diseasementioning
confidence: 92%
“…5A), and the triplication of the aSyn gene are correlated with early onset of the disease [105]. Extensive experimental data indicate that aSyn belongs to the family of natively unfolded proteins, characterised by a lack of typical secondary structures and thus of tightly packed tertiary structure [106]. A recent study has, however, suggested that it might form, in the cell, a dynamic tetramer that is not prone to aggregation [107].…”
Section: Human A-synuclein and Parkinson's Diseasementioning
confidence: 99%